2013
DOI: 10.2355/isijinternational.53.2160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Niobium and Vanadium Additions on the As-Cast Microstructure and Properties of Hypoeutectic Fe–Cr–C Alloy

Abstract: The effect of niobium and vanadium additions (0.5 mass% and 2 mass%) on the as-cast microstructure and properties of hypoeutectic white cast iron containing 19 mass% Cr and 2.9 mass% C, has been examined. NbC carbides present in the structure of tested Fe-Cr-CNb alloys, due to their characteristic morphology, show higher wear resistance and toughness than M7C3 carbides. Increasing amount of this type of carbides, caused by the increase of niobium in the alloy, contributes to the improvement of wear resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 28 publications
6
27
1
6
Order By: Relevance
“…Note that the predicted and measured amounts of each phase are close, but a small difference was noticed since the real material does not solidify under equilibrium conditions as predicted by the software. The observed microstructure has been widely reported by several authors [12,[17][18][19][20][21][22][23] for niobium alloyed white irons. For these measurements, the matrix was considered to be fully austenitic; however, it is well known that some martensitic transformation follows the cooling down process after solidification.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…Note that the predicted and measured amounts of each phase are close, but a small difference was noticed since the real material does not solidify under equilibrium conditions as predicted by the software. The observed microstructure has been widely reported by several authors [12,[17][18][19][20][21][22][23] for niobium alloyed white irons. For these measurements, the matrix was considered to be fully austenitic; however, it is well known that some martensitic transformation follows the cooling down process after solidification.…”
Section: Methodssupporting
confidence: 78%
“…To get primary vanadium carbides, at least vanadium amounts of 5% are necessary, other way vanadium only reinforces the M 7 C 3 carbide [14][15][16]. In the case of niobium, most works studying the effect of this carbide-forming element are limited to amounts of less than 3% [11,12,[17][18][19][20][21][22][23] but up to 5% have been also produced along with high amounts of Mo and W [24]. Niobium forms primary carbides in the liquid and are later enclosed by austenite upon solidification; the size and distribution of which depends on the solidification rate (thickness of the casting).…”
Section: Introductionmentioning
confidence: 99%
“…These Nb carbides act as heterogeneous nuclei of the M 7 C 3 carbides. Filipovic et al [9,10], also observed the refinement effect of Nb in hypoeutectic white cast iron. The authors explained that besides heterogeneous nucleation, NbC limits austenitic primary dendrites growth due to a pin effect of the NbC in the matrix.…”
Section: Methodsmentioning
confidence: 88%
“…As these elements additions also affect the alloy hardenability, ferrite or martensite can form in the matrix along with austenite. Notably, the positive effects of Nb additions on the microstructure of both hypo and hypereutectic white cast irons for potential abrasive applications have been widely demonstrated [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…7) Titanium and niobium were used to improve the wear resistance by forming the harder carbides. [8][9][10] Different from the titanium and niobium, silicon was rejected from forming carbides and mostly dissolved in the matrix. In the medium and high carbon high strength steel by applying quenching-portioning -tempering treatment (QPT), the addition of Si with high content (1.5-2.0 wt.%) was used to suppress the precipitation of cementites during portioning process and enhance the carbon partitioning from martens-…”
Section: Introductionmentioning
confidence: 99%